(untitled) (Jurnal SPEKTRUM, 2026)
As vital facilities, hospitals require a highly reliable and secure electrical power supply to ensure uninterrupted 24-hour operations, specifically in critical care zones such as operating theaters and Intensive Care Units (ICUs). Interruptions in power supply can lead to fatal outcomes. This study aims to design an electrical installation system that is optimal, efficient, and compliant with safety standards outlined in the Minister of Health Regulation No. 24 of 2016 and the General Electrical Installation Requirements (PUIL) 2011. Utilizing a quantitative descriptive method with a case study approach, data were collected via building blueprint documentation and field observations. The analysis encompassed installed load calculations, the selection of protection devices, and the determination of technical specifications for main and backup power systems. The findings reveal a total planned peak load of 1,549.7 kVA. Consequently, the installation of two 1,250 kVA transformers is recommended. The study concludes that reliability and safety must be prioritized over cost efficiency in hospital power planning. The proposed design is intended to serve as a technical guideline for establishing robust electrical systems that support the critical functions of healthcare facilities.